High tech engineers: the engines for economic growth - Tasneem, Usmani; Tunku Salha, Tunku Ahmad; Mohd. Zukime, Mat Junoh (Universiti Malaysia Perlis, 2009)
Organized by Centre for Communication Skills and Entrepreneurship UniMAP in collaboration with The Ministry of Higher Education Malaysia, 5th - 6th December 2008 at Putra Palace Hotel, Perlis.